Evaluation of Teicoplanin Trough Values After the Recommended Loading Dose in Children With Associated Safety Analysis. Issue 4 (April 2017) - Yamada, Takaaki; Kubota, Toshio; Yonezawa, Mahoro; Nishio, Hisanori; Kanno, Shunsuke; Yano, Takahisa; Kobayashi, Daisuke; Egashira, Nobuaki; Takada, Hidetoshi; Hara, Toshiro; Masuda, Satohiro
Abstract : Background: This study evaluated whether the recommended teicoplanin loading dose (3 loading doses of 10 mg/kg every 12 hours) achieves a 15–30 μg/mL trough levels in 26 children (2−16 years). In addition, we examined the incidences of renal impairment and hepatic dysfunction in children treated with teicoplanin. Methods: This retrospective study was conducted between October 2008 and March 2014. Results: The percentage of patients with a trough level <10 and <15 μg/mL were 15.4% (4/26) and 46.2% (12/26), respectively. There were significant correlations between age and concentration/cumulative loading dose (C/D) ratio ( P = 0.045), serum creatinine and C/D ratio ( P < 0.001) and estimated glomerular filtration rate and C/D ratio ( P = 0.005). Serum creatinine was significantly lower when trough levels were <15 μg/mL compared with ≥15 μg/mL. The incidences of renal impairment and hepatic dysfunction were 2.3% and 5.8%, respectively, with no significant difference between <20 and ≥20 μg/mL trough-level groups. Conclusions: The recommended loading dose may be insufficient to achieve 15–30 μg/mL in children with normal renal function. In addition, the target trough level ≥20 μg/mL for deep-seated infections seems to be safe in children. Abstract : Supplemental Digital Content is available in the text.